A double win: practice and participation in an action learning facilitators' set. (4th May 2019) - Wilson, Nicola; Dewis, Caragh
ABSTRACT: This account of practice shares insights from past and present members of a self-facilitating action learning set, where each of the members is an action learning facilitator. Motivations for joining the set encompassed the opportunity to 'practice what you preach' by being a set member as well as a facilitator, the potential to refine and develop facilitation practices in a safe environment and space for personal development.